Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1097/mrr.0b013e32834f402d
|View full text |Cite
|
Sign up to set email alerts
|

Turkish adaptation of Spinal Cord Independence Measure — version III

Abstract: Various rating scales have been used to assess ability in individuals with spinal cord injury. There is no specific functional assessment scale for Turkish patients with spinal cord injury. The Spinal Cord Independence Measure (SCIM) is a specific test, which has become popular in the last decade. A study was conducted to validate and evaluate the Turkish adaptation of the SCIM III (T-SCIM III). The SCIM III was translated into Turkish. Reliability, (internal consistency, interrater reliability, and test-retes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 9 publications
(24 reference statements)
0
15
0
1
Order By: Relevance
“…The mentioned Study of the Turkish version of SCIM-III H Unalan et al study found SCIM-III to be sensitive to the SCI patient characteristics. 7 In the present study, we included more patients (n = 204) and preferred a different outcome scale. Nevertheless, we believe that more studies would render SCIM-III a test with more validity and reliability leading to more practical fields for its use, and more validation studies would yield more positive results, making SCIM-III a more valuable measurement tool.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mentioned Study of the Turkish version of SCIM-III H Unalan et al study found SCIM-III to be sensitive to the SCI patient characteristics. 7 In the present study, we included more patients (n = 204) and preferred a different outcome scale. Nevertheless, we believe that more studies would render SCIM-III a test with more validity and reliability leading to more practical fields for its use, and more validation studies would yield more positive results, making SCIM-III a more valuable measurement tool.…”
Section: Discussionmentioning
confidence: 99%
“…15 Versions of the SCIM have been shown to be valid and reliable in multicenter studies with satisfying psychometric properties. [3][4][5][6][7][8] Comparatively, the SCIM-III represents the most sensitive, reliable and valid measurement of global disability for individuals with SCI. 1,4,[12][13][14] The ISNCSCI (International Standards for Neurological Classification of SCI) has endorsed a standardized neurological examination as the most accurate way to document impairment in a person with an SCI.…”
Section: Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the same item did not pass the acceptance level for the Italian version of SCIM III [41] or for the English version, when examined in the UK population [42] when the scale was not completed by selfreport but was administered by observation. In the original SCIM III study [43] and the Turkish version [44], Cronbach's a was lower for this particular item but just above the accepted level. This finding may indicate some difficulties with the wording of this item and simplification is needed.…”
Section: Reliabilitymentioning
confidence: 99%
“…Validity was examined by comparing concurrent/criterion validity with part of the EQ-5D and not the FIM, as done in previous studies [41,43,44]. For both versions, the correlation between the two scales on the self-care subscales was strong though not as strong as for the other studies when the FIM was used for comparison [41,43,44].…”
Section: Validitymentioning
confidence: 99%